IMPLICATIONS OF IMPLEMENTING BEHAVIOR CHANGES IN ABUSE OF DOMINANT POSITION BASED ON BUSINESS COMPETITION LAW - Hanif, Muhammad Fauzan; Sudaryat, Sudaryat; Suryamah, Aam (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
Abuse of a dominant position is one type of violation that can provide an opportunity to change behavior. The mechanism for providing behavioral change in the abuse of a dominant position has implications for the KPPU, the reported party, and competing business actors. In terms of providing an opportunity to change behavior, the Commission Council considers the type of violation, the time of the violation and the losses caused by the violation. There is no further explanation regarding the criteria for providing an opportunity to change behavior, so legal construction is needed. This research was carried out using a normative juridical approach. Specifications: This research is descriptive analytical in nature, namely the data obtained will be described in this research by providing an overview of legal problems, the legal system and reviewing or analyzing them according to the needs of the research. The results of the research show the implications that arise in providing behavioral changes for violations of abuse of a dominant position which are contrary to the principle of legal certainty. Changes in behavior in the abuse of a dominant position will open up opportunities for the reporter to design abuse strategies in the future with different strategies. Per se approach indicators are needed to perfect the legal construction of providing behavioral changes for abuse of a dominant position. The KPPU can apply an alternative approach by carrying out analysis if the perpetrator abuses a dominant position at the same time committing a violation that meets the elements in another article, behavior change can be rejected.